A mechanistic analysis of density dependence in algal population dynamics - Borlestean, Adrian; Frost, Paul C.; Murray, Dennis L. (Frontiers in Ecology and Evolution, 2015)
Population density regulation is a fundamental principle in ecology, but the specific process underlying functional expression of density dependence remains to be fully elucidated. One view contends that patterns of density dependence are largely fixed across a species irrespective of environmental conditions, whereas another is that the strength and expression of density dependence are fundamentally variable depending on the nature of exogenous or endogenous constraints acting on the population. We conducted a study investigating the expression of density dependence in Chlamydomonas spp. grown under a gradient from low to high nutrient density. We predicted that the relationship between per capita growth rate (pgr) and population density would vary from concave up to concave down as nutrient density became less limiting and populations experienced weaker density regulation. Contrary to prediction, we found that the relationship between pgr and density became increasingly concave-up as nutrient levels increased. We also found that variation in pgr increased, and pgr levels reached higher maxima in nutrient-limited environments. Most likely, these results are attributable to population growth suppression in environments with high intraspecific competition due to limited nutrient resources. Our results suggest that density regulation is strongly variable depending on exogenous and endogenous processes acting on the population, implying that expression of density dependence depends extensively on local conditions. Additional experimental work should reveal the mechanisms influencing how the expression of density dependence varies across populations through space and time.